In-situ remediation of heavy metal contaminated sites through mechanical stabilization using industrial waste products - Raja, Ramiz; Pal, Supriya; Karmakar, Arindam (Journal of Environmental Engineering and Landscape Management, 2022)
The present study aimed to assess the stabilization performance of fly ash, blast furnace slag and quick lime for heavy metals in contaminated soil at a landfill site at Kolkata, West Bengal, India. The physical properties and strength parameters of the contaminated soil substantially increased after additives application. Moreover, the heavy metal concentrations in the leachate of the polluted soil were found almost nil after optimum blending of the additives mechanically with the soil and post-curing for 7 days. The numerical modeling studies were also carried out using PLAXISTM 3D software to ascertain the improvement of safety factor and deformation caused at the foundation level of an embankment constructed on such stabilized soil. The vertical displacement of the embankment founded on stabilized soil reduced from 194.3 to 136.3 mm and the safety factor of the embankment slope (1 V:1.5 H) increased from 2.5 to 3.2 under drained condition.